2019
DOI: 10.1364/ome.10.000076
|View full text |Cite
|
Sign up to set email alerts
|

Deterministically fabricated spectrally-tunable quantum dot based single-photon source

Abstract: Spectrally-tunable quantum light sources are key elements for the realization of long-distance quantum communication. A deterministically fabricated single-photon source with a photon extraction efficiency of η =(20 ± 2) %, a maximum tuning range of ΔE =  2.5 meV and a minimum g(2)(τ = 0) = 0.03 ± 0.02 is presented. The device consists of a single pre-selected quantum dot (QD) monolithically integrated into a microlens that is bonded onto a piezoelectric actuator via gold thermocompression bonding. Here, a thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…Therefore, the effect of creep on the wavelength stability is an important issue to address. One can efficiently stabilize the emission wavelength, as it was reported for quantum light emitting diode 6 and later also realized for deterministically fabricated InAs/GaAs QD microlense, 12 wavelength stability are shown in the Table 1. Evaluation of the recorded µPL time trances yield that best spectral stabilization with an standard deviation of the emission wavelength (energy) of 5.6 pm (4.1 µeV) could be achieved for PG = 100 and IT = 0.01 s. Moreover, we found that by increasing PG, the stabilization time decrease.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Therefore, the effect of creep on the wavelength stability is an important issue to address. One can efficiently stabilize the emission wavelength, as it was reported for quantum light emitting diode 6 and later also realized for deterministically fabricated InAs/GaAs QD microlense, 12 wavelength stability are shown in the Table 1. Evaluation of the recorded µPL time trances yield that best spectral stabilization with an standard deviation of the emission wavelength (energy) of 5.6 pm (4.1 µeV) could be achieved for PG = 100 and IT = 0.01 s. Moreover, we found that by increasing PG, the stabilization time decrease.…”
mentioning
confidence: 82%
“…9,10 This parameter can possibly be increased in the future by applying the present manufacturing method to sources based on circular Bragg resonators that promise broadband photon extraction efficiency up to η = 95% in the telecom O-band. 11 Noteworthy, and in contrast to previous work on piezoelectric tuning of QD-micromesas emitting in the 930 nm range, 12 To demonstrate strain-tuning and to quantify the corresponding spectral shift, the QD emission is studied in dependence of the applied voltage to the piezoelectric actuator. The applied voltage was varied from -400 V to +400 V, which corresponds to an electric field F of -13.4 kVcm -1 to +13.4 kVcm -1 , and results in a spectral tuning range of 0.5 nm for the present sample, as shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent progress in growth and manipulation of nanometric heterostructures has indeed demonstrated the analogy between atoms and solid-state zero-dimensional systems to impressive levels, so that despite emerging in the quantum optics realm decades after natural atoms, QD-based emitters for many purposes not only match but potentially may also surpass their atomic counterpart [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…В настоящее время большой интерес проявляется к созданию приборов для управления одиночными фотонами [1][2][3][4][5][6][7][8][9] и нейроморфных вычислений, использующих в качестве излучателей полупроводниковые гетероструктуры с пониженной размерностью [10][11][12]. Наилучшими кандидатами на роль активных областей для излучателей в таких системах являются квантовые точки (КТ).…”
Section: Introductionunclassified